Using Digital Learning Objects for Instructional Support for Faculty in Agricultural Sciences: A Pilot Study - Hanwen Dong; Maggie Albro (Issues in Science and Technology Librarianship)
This pilot study explores how agricultural sciences faculty utilize Digital Learning Objects (DLOs) in their courses and collaborate with librarians to improve students’ information literacy skills. The researchers conducted in-depth interviews with 14 agricultural sciences faculty members at two land-grant institutions in the United States. The identified key themes from the interviews include the current use of DLOs, challenges in their implementation, and the impact on student learning outcomes. Findings reveal that faculty recognize the value of DLOs for fostering independent learning and improving information literacy skills. However, there are challenges related to technical issues and the need for ongoing librarian support. The study highlights not only the importance of collaboration between faculty and librarians in developing effective DLOs, but also DLOs’ potential to meet the evolving instruction needs in agricultural education. These insights can guide future efforts to enhance the role of DLOs in academic settings, ultimately contributing to a more information-literate and capable agricultural workforce. The findings of the study will also benefit librarians who liaise with agricultural sciences faculty or are responsible for DLO creation.